Faith Integrated English Pedagogy for Generation Z Learners in Islamic Boarding Schools - Dhian Marita Sari; Nunun Indrasari (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This study explores how English teachers in Indonesian Islamic boarding schools adapt their pedagogical practices to the learning characteristics of Generation Z students while maintaining religious and cultural values. The research was conducted at three pesantren, Darul Fikri, Hidayatullah Bangka Belitung, and Ibnu Qoyyim, to examine how teachers address the challenges of teaching digital native learners in educational environments with limited technological access. This study employed a qualitative descriptive design involving six English teachers and eighteen students selected through purposive sampling. Data were collected through semi-structured interviews, classroom observations, and document analysis, and were analyzed using thematic analysis. The findings reveal four major themes. First, Generation Z students prefer interactive, visual, collaborative, and emotionally supportive learning experiences. Second, teachers adapt their instruction through student-centered strategies such as gamification, storytelling, collaborative learning, and contextual teaching linked to students’ daily pesantren experiences. Third, pedagogical innovation is constrained by rigid curricula, limited digital resources, and institutional regulations. Fourth, students respond positively to empathetic and contextually relevant teaching approaches that increase engagement and communicative confidence. This study contributes to English Language Teaching (ELT) literature by proposing a faith-integrated pedagogical adaptation model for Generation Z learners in pesantren contexts. The findings demonstrate that emotional intelligence, contextual relevance, and spiritual alignment can effectively sustain learner engagement even in digitally constrained educational settings. The study highlights the importance of balancing pedagogical innovation with religious and cultural values in faith-based education.